Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.30955/gnj.002522
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting PM10 levels using ANN and MLR: A case study for Sakarya City

Abstract: In this study, potential of neural network to estimate daily mean PM10 concentration levels in Sakarya city, Turkey as a case study was examined to achieve improved prediction ability. The level and distribution of air pollutants in a particular region is associated with changes in meteorological conditions affecting air movements and topographic features. Thus, meteorological variables data for a two-year period for Sakarya city which is located in most industrialized and crowded part of Turkey were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 17 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Another study proved that the ANN model is better in the prediction of particulate matter in Hong Kong, which is in agreement with our findings [72]. Prediction of PM 10 in Sakarya City in Turkey has proved that the nonlinear model (MLP) outperforms the linear model (MLR) with vast differences in the R 2 of 0.84 and 0.32, respectively [73]. Similarly, a previous study in the development of prediction model in industrial area confirmed that the MLP model is able to increase the accuracy by 29.9%, and can reduce the error by 69.3% as compared to the MLR model [35].…”
Section: Models Evaluation and Selectionsupporting
confidence: 90%
“…Another study proved that the ANN model is better in the prediction of particulate matter in Hong Kong, which is in agreement with our findings [72]. Prediction of PM 10 in Sakarya City in Turkey has proved that the nonlinear model (MLP) outperforms the linear model (MLR) with vast differences in the R 2 of 0.84 and 0.32, respectively [73]. Similarly, a previous study in the development of prediction model in industrial area confirmed that the MLP model is able to increase the accuracy by 29.9%, and can reduce the error by 69.3% as compared to the MLR model [35].…”
Section: Models Evaluation and Selectionsupporting
confidence: 90%
“…However, only two methods were found to be frequently used. The first method was a min-max normalization that used the minimum and the maximum values of each feature to change the original data to a new range (Sabri & Tarek, 2012;Özdemir & Taner, 2014;Fu et al, 2015;Zu et al, 2017;Ceylan & Bulkan, 2018;V. Yadav & Nath, 2018).…”
Section: Data Scaling and Data Normalizationmentioning
confidence: 99%
“…• The linear perception of ANN had lower performance than the MLP-ANN because of their simple structure and inability to predict the complex problem (Perez & Reyes, 2002). • The MLR was more frequently implemented when being compared with the MLP-ANN but had lower performance (Alam & McNabola, 2015;Biancofiore et al, 2017;Cai et al, 2009;Ceylan & Bulkan, 2018;Chaloulakou et al, 2003;Gualtieri et al, 2018;Li et al, 2017;Liu et al, 2015;McKendry, 2002;Özdemir & Taner, 2014;Papanastasiou et al, 2007;Slini et al, 2006;Vlachogianni et al, 2011;Voukantsis et al, 2011;Zu et al, 2017). Interestingly, only one research article argued that the MLR performed slightly better than the ANN (Russo et al, 2015).…”
Section: Comparison Of Model Performancementioning
confidence: 99%
“…MLR is a popular statistical model for comparing the model performance with the ANN, but the results showed that MLR is less effective than ANN [17][18][19][20]. ARIMA is a common model for time-series data.…”
Section: Introductionmentioning
confidence: 99%